2001
DOI: 10.1007/s004280100530
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ fibrocytes in invasive ductal carcinoma, ductal carcinoma in situ, and benign breast lesions

Abstract: The present study was undertaken in order to elucidate the question of whether the distribution of stromal CD34+ fibrocytes and smooth muscle actin (SMA)-reactive myofibroblasts differs between benign and malignant lesions of the breast. We investigated a total of 31 ductal carcinomas and 27 specimens with benign lesions of the breast (ductal hyperplasia, sclerosing adenosis, fibroadenoma, phyllodes tumor) and compared the distribution of CD34+ fibrocytes and SMA-reactive myofibroblasts. The stroma of normal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
2
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 20 publications
(30 reference statements)
13
115
2
5
Order By: Relevance
“…19,21 In the stromal compartment of normal breast and benign and malignant breast lesions, the distribution of NGFR is strikingly similar to that described for CD34. 39,45,46 In fact, NGFR was consistently expressed by intralobular (myo)fibroblasts, stromal cells of benign biphasic neoplasms and in pseudoangiomatous stromal hyperplasias, but largely negative in the stromal compartment of invasive tumours. 39,45 Our findings corroborate those of Chauhan et al, 39 giving further evidence for the existence of more than one type of fibroblast in normal breast and in the stromal compartment of breast lesions.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 In the stromal compartment of normal breast and benign and malignant breast lesions, the distribution of NGFR is strikingly similar to that described for CD34. 39,45,46 In fact, NGFR was consistently expressed by intralobular (myo)fibroblasts, stromal cells of benign biphasic neoplasms and in pseudoangiomatous stromal hyperplasias, but largely negative in the stromal compartment of invasive tumours. 39,45 Our findings corroborate those of Chauhan et al, 39 giving further evidence for the existence of more than one type of fibroblast in normal breast and in the stromal compartment of breast lesions.…”
Section: Discussionmentioning
confidence: 99%
“…+ fibrocytes (CD34 is a 110 kDa surface antigen selectively expressed on human haematopoietic progenitor cells) originating from myeloid precursors in the bone marrow were considered as a source of myofibroblasts in cancer of the colon [129], pancreas, [130], and breast [131]. Experimental studies have shown that CD34 + fibrocytes are attracted by the secondary lymphoid chemokine CCL-21, a ligand of the CCR7 chemokine receptor, and invade sites of tissue damage in vivo.…”
Section: The Origin Of Myofibroblastsmentioning
confidence: 99%
“…This study aimed to determine whether loss of CD34 is specific for invasive disease in the breast also (as has already been proved in other organs). An indication to this conclusion has been provided by some earlier researchers [11][12][13][14][15][16][17][18][19][20][21][22]. Bucala R et al also postulated that since CD34+ fibrocytes are capable of collagen I and collagen III synthesis, it seems to be likely that this cell type may be involved in the process of stromal remodeling in breast cancer [23].…”
Section: Introductionmentioning
confidence: 91%
“…"It has been suggested that there is an inverse relation between CD34 expression and myofibroblastic differentiation" [11].…”
Section: Introductionmentioning
confidence: 99%